Utilization of Natural Materials as a Preparation of Acne Face Mask Gel: A Narrative Review - Ananda Kamalia; Rizkya Roswati; Sri Tantia Dinita; Nia Yuniarsih (Archives of The Medicine and Case Reports, 2022)
The current treatment for acne disorders is generally adjusted to the grade of acne, where the use of exfoliating agents to antibiotics is the current choice. This has a serious impact on the health of facial skin, where allergies, irritation, and clogged pores of the facial skin become negative impacts that often occur. Exploration of new modality therapy is a solution to provide the best treatment for facial skin. This literature review aims to discuss the use of natural ingredients such as face masks to treat acne. Some natural plant ingredients that have anti-acne benefits are used as basic ingredients in the formulation of facial gel masks for acne-prone skin, including Carica papaya L, Curcuma zedoaria, Citrus sinesis (L) osbeck, Nephelium lappaceum L, and Leucaena leuccocephala.